Vol. 3, No. 1, September 2021 - Bodhy Widodo (Scientia Regendi, 2021)
Indonesia as a sovereign state recognizes the existence of human rights (HAM) in Article 28 E paragraph (3) of the 1945 Constitution of the Republic of Indonesia (UUD 1945), which reads: